2020
DOI: 10.1186/s12882-020-02178-w
|View full text |Cite
|
Sign up to set email alerts
|

Overhydration and low serum prealbumin predict peritoneal dialysis-related peritonitis in continuous ambulatory peritoneal dialysis patients

Abstract: Background In this study, we focused on the role of overhydration (OH) and low serum prealbumin concentration in predicting peritonitis in continuous ambulatory peritoneal dialysis (CAPD) patients over a 3-year period. Methods We measured serum prealbumin concentration and OH by body composition monitor in 278 CAPD patients (159 males and 119 females) with a mean age of 46 years and a median peritoneal dialysis (PD) duration of 21 months. Cases of PD-related peritonitis were collected over 3 years. Results A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Multiple studies reported that serum pre‐albumin was an independent and best predictor of mortality in PD patients, and was more sensitive than albumin [ 36 ]. Dao et al also showed that in patients on continuous PD, low serum pre‐albumin was predictive of PD‐related peritonitis [ 37 ].…”
Section: Other Novel Parametersmentioning
confidence: 99%
“…Multiple studies reported that serum pre‐albumin was an independent and best predictor of mortality in PD patients, and was more sensitive than albumin [ 36 ]. Dao et al also showed that in patients on continuous PD, low serum pre‐albumin was predictive of PD‐related peritonitis [ 37 ].…”
Section: Other Novel Parametersmentioning
confidence: 99%